Knowledge and practice of formal physicians regarding control and prevention of TB in light of national guidelines - Islam, Qazi Shafayetul; Ahmed, Syed Masud; Islam, Md. Akramul; Islam, Shayla (BRAC Research and Evaluation Division (RED), 2019)
The study explored the current knowledge and practice of interns and general physicians regarding control and prevention of tuberculosis in light of national guidelines. The study was conducted on 13 public and seven private medical college hospitals to collect information from intern physicians, and the general physicians who were practicing in a half kilometer radius of each medical college. A total of 1474 intern physicians and 539 general physicians participated in the study. It was a self-administered survey. About three-fourth of physicians (75%) had knowledge about community based TB control programme. However, Only 36% reported that they knew details about the programme. Despite majority (90-96%) had comprehensive knowledge on TB as a major public health problem in Bangladesh but, many of them (70%) did not express their intention to become involved in TB control. Because 92% did not know that the main vision of TB control programme (TB would no more as a public health problems). The knowledge score was constructed on 17 knowledge variables regarding basic and clinical aspects of TB. 61% of intern physicians had adequate knowledge (mean scores~ 1 0.82) unlike among general physicians where as it was 44%, (p<0.0001). The logistic regression depicts that physicians were more likely to be knowledgeable when they were aware of national guidelines for TB control (AOR 2.16, 95% Cl: 1.36, 3.44), when physician had access to more sources of TB information (AOR 1.43, 95%CI: 1.1 0, 2.36), more duration of TB information sharing (>6 hours) (AOR 3.10, 95% Cl: 2.37,.07). We also found, male physicians were less knowledgeable than that of female physician (AOR 0.77, 95% Cl: 0.63, 0.95). The majority of physicians treated TB suspects with antibiotics (40-6%), and only advised for further tests (39-44%). Majority of interns and general physicians did not follow the NTP guideline of three mandatory visits of patients to health facilities for follow up during treatment period. Still significant proportion of physicians (37 -50%) did not refer TB patients and suspects for further investigations and services to the nearest DOTS corner. Majority would not ask for X-ray for further investigation when they got two negative results out of three sputum examinations. Onethird of physicians (39%) perceived that medical curriculum was not sufficient for practicing TB (39%). A great majority of physicians (75%) confessed that they sought TB information beyond classroom. In conclusion, they seriously lacked knowledge regarding its clinical aspect of TB management in light of national guidelines. Most of them did not know the details activities of TB control programmes, and did not follow the national guidelines in managing TB patients. Activities of National TB progamme should be visible more. Guidelines should be incorporated in the final year medical curriculum. Appropriate tools, protocols and customized training packages need to be developed for intern and general physicians.